Correlation between Locus of Control and Personal Responsibility through Pro-Environmental Intention in High School Students - Ahsanul Akhsan Dasi; Mieke Miarsyah; Rusdi Rusdi (Indonesian Journal of Science and Education (IJOSE), 2019)
This study aims to know the relationship between locus of control (X1), and personal responsibility (X2) wit pro-environmental intention in XI MIPA students at SMAN 8 Makassar, South Sulawesi (Y). Partisipants for study were 120 students. Based on data analysis can be known coeficcient correlation between X1 with Y, coeficcient correlation between X2 with Y and coeficcient correlation between X1 and X2 with Y. Locus of control and personal responsibility has contributed to the pro-environmental intention of 12.7%. Keywords: Environmental, locus of control, personal responbility, pro-environmental intention